2013
DOI: 10.3144/expresspolymlett.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Sensing strain and damage in polyurethane/MWCNT nano-composite foams using electrical measurements

Abstract: The addition of carbon nano-fillers (nanofibers (CNF), nanotubes (CNT) etc.) into plastics has been shown to affect the various properties of the resulting material and effectively increase the electrical conductivity of the system by several orders of magnitude [1]. This is attributed to the formation of a conductive network of the conductive nanofillers, which can be described as a percolated network. The increased electrical conductivity of the nano-reinforced materials has given rise to their use in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 40 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…It was shown that the electrical resistance profile found is a characteristic of all the MWCNT contents and depends on density and conductivity (48).…”
Section: Thermal Sound and Electrical Insulationmentioning
confidence: 99%
“…It was shown that the electrical resistance profile found is a characteristic of all the MWCNT contents and depends on density and conductivity (48).…”
Section: Thermal Sound and Electrical Insulationmentioning
confidence: 99%
“…Modulus deterioration for incremental loading of nano-composite GFRPs as a function of irreversible resistance changes: maximum resistance and residual resistance [60]. 14.5 Demonstration of Nano-Composite Multifunctionality monitoring based on electrical resistance changes has also been demonstrated for foamed nano-composite systems with CNT [63]. Working on addressing primarily Level 2, a number of studies have investigated the use of tomographic approaches to employ the CNT network inside the composite's matrix.…”
Section: Demonstration Of Nano-composite Multifunctionalitymentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] The focus of this work is electronic transport in nanocomposites. In that regard, an accurate understanding of how CNTs modify electrical properties of an otherwise insulating matrix, can extend their utilization to applications such as electromagnetic interference shielding [41][42][43][44][45][46][47][48], electrostatic reduction [13], and strain sensing for structural health monitoring [27,[49][50][51][52][53][54][55][56][57][58][59][60][61], to mention some examples.…”
Section: Introductionmentioning
confidence: 99%